Penerapan Model Cooperative Learning Tipe Tebak Kata Dalam Meningkatkan Hasil Belajar Siswa pada Muatan Pembelajaran IPA pada Kelas IV UPTD SDN 34 Parepare - Musfirah, Musfirah; Yulia; Yusuf, Yunita (UNIB Press, 2022)
The problem in this study is the low learning outcomes of fourth grade students. The problem in this research is how is the process of applying the Guessing Type Cooperative Learning model and whether applying the Guessing Type Cooperative Learning model to science learning content can improve student learning outcomes in class IV UPTD SDN 34 Parepare. The approach used in this research is a qualitative approach. This study focuses on the process and student learning outcomes on the material wealth of energy resources in Indonesia by applying the Cooperative Learning Model Type Guess the Word. Data collection techniques used are observation, tests and documentation. The research subjects were teachers and students with a total of 21 students consisting of 15 male students and 6 female students. Data analysis techniques are data condensation, data presentation and conclusion drawing. The implementation of this research was carried out in two cycles starting with pre-action activities, then each cycle consisted of 4 stages, namely planning, implementation, observation and reflection.